2020
DOI: 10.3389/fphys.2020.550102
|View full text |Cite
|
Sign up to set email alerts
|

Altered GDF15 and FGF21 Levels in Response to Strenuous Exercise: A Study in Marathon Runners

Abstract: Background: Recreational marathon runners face strong physiological challenges. Assessment of potential biomarkers for the biological responses of runners will help to discriminate individual race responsiveness and their physiological consequences. This study sought to analyze the changes in the plasma levels of GDF15 and FGF21, novel endocrine factors related to metabolic stress, in runners following the strenuous exercise of a marathon race. Methods: Blood samples were obtained from eighteen male runners (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…It has been shown that serum FGF21 level was significantly increased in 14 healthy subjects who cycled for 45 min [ 35 ]. Campderrós et al [ 55 ] measured serum FGF21 in 18 male runners before and after a marathon and found that at the end of the race, the FGF21 level was 20 times higher than that before the race. However, the serum FGF21 level reduced after 36 and 12 weeks of exercise in humans and animals with obesity [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that serum FGF21 level was significantly increased in 14 healthy subjects who cycled for 45 min [ 35 ]. Campderrós et al [ 55 ] measured serum FGF21 in 18 male runners before and after a marathon and found that at the end of the race, the FGF21 level was 20 times higher than that before the race. However, the serum FGF21 level reduced after 36 and 12 weeks of exercise in humans and animals with obesity [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, exercise is one of the best therapeutic options to treat or prevent insulin resistance and type 2 diabetes [ 87 ]. We and others have shown that aerobic exercise as well as resistance exercise increase circulating GDF15 in humans [ 27 , 88 , 89 , 90 , 91 , 92 ]. Notably, GDF15 increases during and also in recovery from exercise.…”
Section: Gdf15 As a Myokine—signaling And Physiological Significancementioning
confidence: 99%
“…For example, after 4 h of intense cycling, GDF15 increased from baseline levels of ~0.3 ng/mL to ~2 ng/mL in elite male triathletes [ 27 ]. Similarly, circulating GDF15 increased from ~0.5 ng/mL to ~1.6 ng/mL after a 130 km long cycling race in a study cohort of mostly middle-aged men [ 89 ] or from ~0.35 ng/mL to ~1 ng/mL in middle-aged male runners after completing a marathon in 3–4 h [ 88 ].…”
Section: Gdf15 As a Myokine—signaling And Physiological Significancementioning
confidence: 99%
“…Surely, many other processes that are induced under these conditions can modulate this immune response. These are mediated by an array of soluble mediators including growth factors, cytokines, and myokines (Bay & Pedersen, 2020 ; Campderrós et al, 2020 ). Apart from these mediators, the immune response to exercise is also affected by changes in the microbiota (Adams et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%